Effect of temperature on dunit structure in Jorong Tongar, Nagari Aur Kuning, Kecamatan Pasaman, Kabupaten Pasaman Barat West Sumatra - Melinda Wardani (Department of Physics – Universitas Negeri Padang UNP, 2014)
This research was conducted to find out the structureof the mineral dunite before and after calcination. This important research is done to increase the utilization of dunite. Determination of the structure of the dunite use characterization x-ray Diffraction (XRD). Dunite is heated with temperature variation, to see its effect when given the variations in temperature. The results obtained indicate the given temperature variation of structure of hexagonal dunite turned into orthorombik, with concentrations growing against the increase in the temperature of calcination.